A REVIEW OF INFLUENCE FROM FIRST AND SECOND LANGUAGE AS SYNTAX INTERFERENCE IN THE GERMAN LANGUAGE - Robe'ah Yusuf; Mariyati Mohd Nor; Zarima Mohd Zakaria; Norjietta@Julita Taisin, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The syntax is the field of studies in constructing sentences which is the knowledge in a language that studies the form, structure, and sentence construction. In general, syntax is involving the system that studies the rule and categories in the foundation of constructing sentences for a language. The syntax is not only research on the process of constructing sentences but also including the laws that determine how the words arranged in the sentences. Thus, the objective of this article is to study the literature review on constructing sentences in the German language that influenced by the first and second languages. Some of the researchers find that the first and second language is named by syntax interference. Based on the qualitative methodology, this article recorded seven articles from the years 2015 until 2020. The research on syntax which focusing on the German language is needed because this language is one of the subjects learned in selected schools and universities in Malaysia. Hence, it is hoped that this paper can enlighten other researchers on the German language syntax.